1994
DOI: 10.1002/tera.1420490211
|View full text |Cite
|
Sign up to set email alerts
|

Teratologic evaluation of rats prenatally exposed to pulsed‐wave ultrasound

Abstract: While there are no known risks associated with diagnostic ultrasound, uncertainty about the safety of prenatal ultrasound exposure remains. The purpose of the present experiment was to evaluate the teratogenic potential of pulsed-wave (pw) ultrasound in rats, in the absence of maternal anesthesia or restraint. Pregnant CD rats, trained to remain immobile in a water-filled ultrasound exposure tank, were scanned with 3-MHz pw ultrasound at levels of 0, 2, 20 or 30 W/cm2 ISPTA (spatial peak, temporal average inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Effects of diagnostic US exposure on fetal body weight have also been reported in some studies, but not in others (Fisher et al 1994). Previous investigations of bioeffects associated with high-frequency US biomicroscopy have included the anterior segment of the rabbit eye, in which exposures with the focal point placed on the cornea resulted in no evidence of changes in the tissue (50 MHz, IM SPTA.3 34.2 mW/cm 2 , 30 min, 10-kHz pulse-repetition frequency, PRF; Silverman et al 2001).…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…Effects of diagnostic US exposure on fetal body weight have also been reported in some studies, but not in others (Fisher et al 1994). Previous investigations of bioeffects associated with high-frequency US biomicroscopy have included the anterior segment of the rabbit eye, in which exposures with the focal point placed on the cornea resulted in no evidence of changes in the tissue (50 MHz, IM SPTA.3 34.2 mW/cm 2 , 30 min, 10-kHz pulse-repetition frequency, PRF; Silverman et al 2001).…”
Section: Introductionmentioning
confidence: 90%
“…The data on the effect of in utero exposure of mice to diagnostic US is highly inconsistent, with some studies reporting effects on embryonic/fetal viability and/or increased malformation rates, but others have found no effects (reviewed in Fisher et al 1994). Effects of diagnostic US exposure on fetal body weight have also been reported in some studies, but not in others (Fisher et al 1994).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…In a collaborative project with ultrasound engineers and ultrasound physicians, we developed an ultrasound exposure system for rats (Smith et al, 1990). We used the system to test for teratogenic effects of continuous (Vorhees et al, 1991b) or pulsed ultrasound (Fisher et al, 1993) and in both cases found no teratogenicity in the CWM under standard lighting. We next used the same system to evaluate the neurobehavioral effects of prenatal continuous or pulsed wave ultrasound and again found no effects in the CWM under standard room lighting (Vorhees et al, 1994c; Fisher et al, 1996).…”
Section: Assessing Navigation In Rodentsmentioning
confidence: 99%
“…Applied to medicine, this forms the basis of the ‘ primum non nocere ’ (first do no harm) approach as well as the ALARA (as low as reasonably achievable) principle. Effects of insonating waves have been demonstrated in animals10–16 and investigations into several biological effects in humans have been documented in the literature, the conclusions of which are summarized in the AIUM epidemiology statement17. There is very little information on energy output and exposure in clinical obstetric ultrasound.…”
Section: Summary Of Presentations At the Florence Isuog/wfumb Workhopmentioning
confidence: 99%